Thermal behavior of biomass under thermochemical treatment at different air fluxes in an updraft reactor - Kittipass Wasinarom; S. Sungworagarn; P. Sathitruangsak; Wichean Singmai; Kasemsil Onthong (BioResources, 2023)
Thermochemical treatment was investigated experimentally at different air fluxes in an updraft reactor. The test rig was equipped with a special attached door that will open at a specific time step. This unique feature allows investigators to obtain information on the packed bed color variation along the different heights of the reactor that evolves at different points in time. The analysis focused on the temperature dynamics obtained from installed thermocouples with the packed bed color variation at each time step. The investigation was conducted for three different supply air mass fluxes, which were 670, 480, and 190 kg/m2h. The general thermal behavior is addressed in the first part of the paper because it is similar for all different input air mass fluxes. Next, the distinctive operation parameters among different air mass fluxes are discussed; these included the hot spot zone, fuel conversion characteristic, temperature distribution, heat transfer, and kinetic activities along the height of the reactor.
Keywords: Fire dynamics and safety research; Thermochemical Biomass Conversion Processes; Coal Combustion and Slurry Processing